Leituras sobre usuário e uso de informação na Ciência da Informação - Rabello, Rodrigo [UNESP] (Escola de Ciência da Informação da UFMG, 2013)
Considering aspects of international literature in the area of Information Science (IS) regarding need, search, behavior and use of information, this study aims to explore the historical path and interpretations of the concepts of user and use of information, under the support reference of the notions of information system and subject agency. For such, a corpus was formed with 15 literature reviews of the Annual Review of Information Science and Technology - ARIST - which brought a theoretical panorama on the concepts here studied. The analysis of these reviews was tooled with categorizations of the use of information proposed by Rachel Anne Fleming-May, making it possible to situate two initial phases identified, particularized for orbiting a notion of information system, being the first phase characterized by a more static conception of system and the second by a more dynamic meaning. Finally, a third and last phase was found in reading ARIST, which was better visualized after the year 2000. In the first decade of the 21st century, studies started considering, complementarily to previous phases, the agency of subjects from the notions of interaction and context, in actions of use, production and appropriation of information and knowledge.

Considerando aspectos da literatura internacional da área de Ciência da Informação (CI) relacionados aos temas necessidade, busca, comportamento e uso da informação, objetivou-se explorar a trajetória histórica e as interpretações sobre os conceitos usuário e uso de informação, tomando, como referencial de apoio, as noções de sistema de informação e de agência dos sujeitos. Para tanto, foi delimitado como corpus 15 revisões de literatura da Annual Review of Information Science and Technology (ARIST) - que trouxeram um panorama teórico sobre os conceitos estudados. A análise dessas revisões foi instrumentalizada com as tipificações sobre uso de informação propostas por Rachel Anne Fleming-May, que permitiu situar as duas fases iniciais identificadas, que se particularizam por orbitar a noção de sistema de informação, sendo a primeira fase caracterizada por uma concepção mais estática de sistema e a segunda por uma acepção mais dinâmica. Por fim, observou-se, na literatura da ARIST, uma terceira e última fase, que passou a ser mais bem visualizada a partir da década de 2000. Naquela década, os estudos passaram a considerar, complementarmente às fases anteriores, a agência dos sujeitos a partir das noções de interação e de contexto, em ações de uso, produção e apropriação de informação e de conhecimento.
Readings on user and use of information in Information Science
Keywords: Usuário de informação; Uso de informação; Annual Review of Information Science and Technology; Ciência da Informação; Information user; Information use; Annual Review of Information Science and Technology; Information Science